2008
DOI: 10.1007/s00109-008-0410-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced L1CAM expression on pancreatic tumor endothelium mediates selective tumor cell transmigration

Abstract: L1 cell adhesion molecule (L1CAM) is a transmembrane cell adhesion molecule initially defined as a promigratory molecule in the developing nervous system that appears to be also expressed in some endothelial cells. However, little is known about the functional role of L1CAM on endothelial cells. We observed that L1CAM expression was selectively enhanced on endothelium associated with pancreatic adenocarcinoma in situ and on cultured pancreatic tumor-derived endothelial cells in vitro. L1CAM expression of endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…Staining of cells with mAbs and with PE-conjugated secondary antibodies has been described (Mechtersheimer et al, 2001;Issa et al, 2009). …”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Staining of cells with mAbs and with PE-conjugated secondary antibodies has been described (Mechtersheimer et al, 2001;Issa et al, 2009). …”
Section: Flow Cytometrymentioning
confidence: 99%
“…Subsequent work has shown overexpression of L1CAM in a variety of human tumours, in which it is associated with bad prognosis and metastases formation (Thies et al, 2002;Fogel et al, 2003a, b;Boo et al, 2007;Kaifi et al, 2007). Furthermore, L1CAM was detected in tumour-associated endothelium (Issa et al, 2009;Maddaluno et al, 2009). Expression of L1CAM was also described in pancreatic ductal adenocarcinomas (PDACs) (Sebens Muerkoster et al, 2007Geismann et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…S2 F). Finally, although Tie2-Cre mice have been used to target genes expressed in ECs ( 8 ) and L1 expression in the vessels has been reported under pathological conditions ( 10,11 ), no gross vascular defects were noted in Tie2-Cre;L1 f loxed mice.…”
mentioning
confidence: 99%
“…The proangiogenic effect of soluble L1CAM could be abolished by treatment with the L1CAM specific antibody chCE7. Issa et al showed that endothelial cells in PDAC are characterized by elevated L1CAM expression compared to HUVEC cells where L1CAM expression can be induced by TNFIFNor TGF-1 (Issa et al, 2009). Antibody-mediated blockade of L1CAM abolished tube formation and tumor endothelial cell transmigration (Issa et al, 2009).…”
Section: L1cam and Angiogenesismentioning
confidence: 99%
“…Issa et al showed that endothelial cells in PDAC are characterized by elevated L1CAM expression compared to HUVEC cells where L1CAM expression can be induced by TNFIFNor TGF-1 (Issa et al, 2009). Antibody-mediated blockade of L1CAM abolished tube formation and tumor endothelial cell transmigration (Issa et al, 2009). Overall, these data point to a role of L1CAM as a pro-angiogenic factor and the potential of an anti-L1CAM antibody therapy in interfering with tumor angiogenesis (see below).…”
Section: L1cam and Angiogenesismentioning
confidence: 99%